RANCANG BANGUN APLIKASI SIDUMA (SISTEM INFORMASI PENGADUAN MAHASISWA) DI UNIVERSITAS BANTEN JAYA - Yul Hendra; Irma Yunita; Achmad Rifai; Andi Usri Usman; Dedi Juniansha (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
In today’s highly competitive educational landscape, universities must focus on enhancing the quality of services they provide to their students. To effectively understand the needs and desires of students, institutions must actively seek their feedback. However, a common challenge faced at Banten Jaya University is that students often hesitate to share their input regarding service processes. This reluctance stems from the absence of a systematic platform for lodging complaints or feedback.To address this issue. necessity of developing a robust system that can efficiently gather and present student complaints and suggestions. The goal is to deliver quick and accurate reporting that can be utilized by the campus management for evaluation and improvement purposes. The research employs the Agile Method for system development, complemented by data collection techniques such as interviews and direct observations.With the introduction of the Student Complaint System, known as SIDUMA, it is anticipated that all student complaints and reports will be systematically captured. The insights derived from these submissions will enable Banten Jaya University to conduct ongoing evaluations, ultimately striving for excellence in service quality.